Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/advs.202000803
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Emitting Anti‐Counterfeiting Ink Prepared by Anthraquinone‐Modified β‐Cyclodextrin Supramolecular Polymer

Abstract: Intelligent fluorescent materials have been paid more and more attention due to their wide application in information encryption and anti‐counterfeiting materials. Herein, a supramolecular polymer is constructed through the host–guest interaction of anthraquinone‐modified β ‐cyclodextrin (AQ‐ β ‐CD) in aqueous solution. Thanks to the hydrophobic microenvironment of the cyclodextrin cavity and the shielding effect on oxygen molecules, the anthraquinone group, as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The intense peak of [M-Br] + (m/z 1764.4669) fitted well the calculated value (1764.4677), and the distance value between adjacent peaks was 1, which provided convincing evidence for the 1:1 complex formation (Figure S13, Supporting Information). [49] In addition, since the chemical shift of supramolecular polymer would change greatly with the dilution of the polymer, [50] we analyzed the 1 H NMR spectra of G⊂CB[8] at different concentrations. It could be found that signals for protons of G stayed unchanged as G⊂CB [8] was gradually diluted to tenfold, which denied that G⊂CB [8] was a higher-level supramolecular assembly (Figure S14, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The intense peak of [M-Br] + (m/z 1764.4669) fitted well the calculated value (1764.4677), and the distance value between adjacent peaks was 1, which provided convincing evidence for the 1:1 complex formation (Figure S13, Supporting Information). [49] In addition, since the chemical shift of supramolecular polymer would change greatly with the dilution of the polymer, [50] we analyzed the 1 H NMR spectra of G⊂CB[8] at different concentrations. It could be found that signals for protons of G stayed unchanged as G⊂CB [8] was gradually diluted to tenfold, which denied that G⊂CB [8] was a higher-level supramolecular assembly (Figure S14, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Precise control of the solution viscosity and polarity allows regulation of the fluorescence lifetime of eosin. We found that the as-prepared eosin aqueous solutions mixed with different volume ratios of organic solvents were particularly useful for multilevel lifetime encryption with a high-throughput rate of authentication and without the need for complex preparation of reversible emitting anticounterfeiting ink. , …”
mentioning
confidence: 94%
“…We found that the as-prepared eosin aqueous solutions mixed with different volume ratios of organic solvents were particularly useful for multilevel lifetime encryption with a high-throughput rate of authentication and without the need for complex preparation of reversible emitting anticounterfeiting ink. 22,23 RESULTS AND DISCUSSION τm, τ2, and τi, Three Lifetime Parameters. It is generally believed that an organic fluorescent dye only has one fluorescence lifetime.…”
mentioning
confidence: 99%
“…Then the 1 H-NMR was researched more carefully, the protons of CB[8] split into two chemical shift groups, suggesting that the chemical environments of the two ports differed from each other, which provided evidence against the formation of a linear polymer resulting from head-to-tail binding. Because the chemical shift of the protons of a linear supramolecular polymer would change substantially upon dilution of the polymer, [17] we therefore measured the 1 H NMR spectra of 1/CB[8] at various concentrations. We found that the chemical shift for the protons belonging to the guest molecule had no change even when the assembly was diluted nearly 20-fold (Figure S4, Supporting Information); this result also indicates that 1:1 of 1/CB[8] assembly was stable.…”
mentioning
confidence: 99%